Kepadatan Populasi dan Persentase Serangan Hama Tungau Merah Tetranychus Urticae Koch (Acarina : Tetranychidae) pada Tanaman Jeruk Siam (Citrus Nobilis Lour) yang di Perlakukan dengan Akarisida Piridaben 135 g/l - PEBRIANI, NI NYOMAN; WIDANINGSIH, DWI; DARMIATI, NI NENGAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Population Density and Presentage of damage Red Mite Tetranychus urticae Koch (Acarina : Tetranychidae) on Siam Citrus (Citrus nobilis Lour) treated with Acaricide Pyridaben 135 g/l This research was carried out in Sekaan village, Kintamani District, Bangli Regency, from January until March 2018. The study used Randomized Block Design (RAK) with 5 acricide treatments of I, II, III, IV, and control were 0.125 ml / l, 0.25 ml / l, 0.375 ml / l, 0.5 ml / l and 0 ml/l, respectively. Piridaben acaricide had a significant effect on population density and percentage damage of T. urticae. The highest population density and Percentage damage of T. urticae on leaves and fruit was found at control and the lowest at 0.5 ml / l treatment.